Effect of Robot-Assisted Gait Training on Multiple Sclerosis: A Systematic Review and Meta-analysis of Randomized Controlled Trials. (April 2023) - Yang, Fu-An; Lin, Chien-Lin; Huang, Wan-Chien; Wang, Hsun-Yi; Peng, Chih-Wei; Chen, Hung-Chou
Background: In recent meta-analyses, robot-assisted gait training for patients with multiple sclerosis (MS) have yielded limited clinical benefits compared with conventional overground gait training. Objective: To investigate the effect of robot-assisted gait training for patients with MS on clinical outcomes through a systematic review and meta-analysis. Methods: We searched for relevant studies in the PubMed, EMBASE, Cochrane Library, and Physiotherapy Evidence Database databases from their inception to April 7, 2022. We selected studies that (1) included participants with MS, (2) used robot-assisted gait training as the intervention, (3) included conventional overground gait training or another gait training protocol as control treatment, and (4) reported clinical outcomes. Continuous variables are expressed as standardized mean differences with 95% confidence intervals. Statistical analyses were performed using RevMan 5.4 software. Results: We included 16 studies enrolling 536 participants. Significant improvement was observed in the intervention group, with low heterogeneity at the end of the intervention with regard to walking velocity (standardized mean difference [SMD]: 0.38, 95% confidence interval [CI]: [0.15, 0.60]), walking endurance (SMD: 0.26, 95% CI [0.04, 0.48]), mobility (SMD: −0.37, 95% CI [−0.60, −0.14]), balance (SMD: 0.26, 95% CI [0.04, 0.48]), and fatigue (SMD: −0.27, 95% CI [−0.49, −0.04]). The results of subgroup analyses revealed improvements in these outcomes for the intervention group using grounded exoskeletons. No significant differences were noted in all the outcomes between the groups at follow-up. Conclusions: Robot-assisted gait training with grounded exoskeletons exerts a positive short-term effect and is an adequate treatment option for patients with MS.